Gingival Fenestration Defect Treated with Gingivectomy and Gingivoplasty: A Case Report with an 8-year Follow-Up - Kajimoto, Natalia de Campos; Buischi, Yvonne de Paiva; Loomer, Peter Michael; Pola, Natalia Marcumini; Nagata, Maria Jose Hitomi [UNESP]; Bosco, Alvaro Francisco [UNESP] (Wiley-Blackwell, 2021)
Introduction: Gingival fenestration (GF) is scarcely reported in the literature. We present a unique case of GF defect combined with gingivitis and altered passive eruption (APE). Case Presentation: An 18-year-old female patient with gingivitis, APE, and GF in the mandibular left central incisor presented for periodontal treatment. The gingival lesion was successfully treated with basic periodontal therapy gingivectomy, and gingivoplasty and resulted in an excellent aesthetic long-term outcome. This case report shows its 8-year clinical follow-up. Conclusion: There are no earlier reports dealing with the use of gingivoplasty for the treatment of GF, as it is not the usual therapeutic intervention for these defects. Gingivoplasty proved to be effective in treating GF.
Keywords: Diagnosis; gingival overgrowth; gingivitis